Hubungan Empati dengan Perilaku Prososial Siswa SMA di Era New Normal - Giskandi, Jefni; Sano, Afrizal (Current Issues in Counseling, 2023)
Adolescent social interactions benefit greatly from prosocial behavior. Adolescent prosocial behavior, such as being egocentric and unconcerned with their friends, decreased during the new normal era.Empathy is one of the elements that affect prosocial behavior. The three objectives of this study are to (1) describe a picture of student empathy, (2) describe a description of students' prosocial behavior, and (3) determine whether there is a significant relationship between empathy and prosocial behavior among high school students in the new normal era. A quantitative research methodology using a descriptive and correlational approach was used. The population of the study consisted of all 214 students enrolled in SMAN 2 Ranah Pesisir, with 139 students representing as the sample using stratified random sampling. The Likert scale model and the empathy questionnaire were used to collect data on students' prosocial behavior. Percentage and correlation methods utilizing Pearson Correlation Product Moment are used in data analysis. According to the study's findings, student prosocial behavior was in the high category with a percentage of 54.0%, while student empathy was in the high category with a percentage of 68.3%. Additionally, there was a significant positive correlation between these two behaviors, with a correlation coefficient of 0.647 and a significant value of 0.000.